O lugar do gênero na psicanálise: da metapsicologia às novas formas de subjetivação - Felippe Figueiredo Lattanzio (2011)
The dissertation proposes to formulate a psychoanalytical concept of gender, from the study of the considerations of various authors (such as Jean Laplanche, Paulo de Carvalho Ribeiro, Jacques André; Robert Stoller; Judith Butler; Donna Haraway) that approach this object of research. In order to do so, we will, initially, trace a selected history of psychoanalytical theories that have treated the concept of gender, showing its origins and evolution. The criterion for establishing the theoretical cut will be the primacy of otherness: we will privilege the authors that study gender from its intersubjective dimension and as a product of the action of the other on psychism. Such an outline will lead us to exploit the relation between otherness, femininity and repression. Afterwards, we will critically analyze the relation between femininity, passivity and masochism. We will try to understand how the psychoanalytical theories that treat femininity as negativity are inadvertently based on naturalized and metaphysical categories, in which the phallic logic gives to femininity the statute of lack connected to castration and of inexistence. We will propose, thus, a positivation of femininity, that will be made from an utilization of some elements of Nietzsches thoughts and also from that of Deleuze. However, from an interlocution with feminist theory, we will show how any form of essencialization of femininity is problematic, being more interesting to let the concept in a permanent state of opening. The possibilities of overcoming the dualisms of the sex-gender system will be, then, discussed through transgression of hierarchies imposed by this system. After this démarche, the relation between femininity, passivity and masochism will appear as a contingent foundation in the search of a theoretical understanding of gender. In a third moment, we will propose a psychoanalytical concept of gender, in its relation to sex, identification and psychic conflict. Such a concept will be worked on two fronts: on the one hand, we will formulate its metapsychological articulations, in which gender will appear as a fundamental concept of psychoanalytical theory; on the other hand, we will work the vicissitudes that gender identity can assume in masculinity and femininity. Such a path will lead us to propose what we will call a becoming-woman as a virtuality responsible for the emergence of more free and permeable new forms of subjectivation, both masculines and feminines. Next, as a way to exemplify the challenges that impose themselves to theory when it is confronted with subjectivities that apparently contradict the phallic norm, we will analyze transsexuality, aiming to show how the psychosis diagnostic frequently attributed to this condition is inheritor of a theoretical hardening based on the essencialization of the phallic logic. We will locate, on the contrary, transsexuality as the reverse of psychosis, trying not to unlink some stereotypical manifestations of this condition from the social normativity in which it is inserted. At the end of this démarche, we intent to place gender in a central position among Psychoanalysiss concepts, showing its role and importance in the psychic subjects constitution in general and in the emergence of new forms of subjectivation.